A survey on knowledge, attitude and confidence level of adult cardiopulmonary resuscitation among junior doctors in Hospital Universiti Sains Malaysia and Hospital Raja Perempuan Zainab II. Kota Bharu, Kelantan - Fauzi, Mohd Hashairi Hj (2010)
In hospital, junior doctors are often the first to initiate resuscitation attempts. Therefore it is important that they have adequate knowledge, positive attitude and good confidence level in managing cardiac arrests according to the current guidelines for resuscitation. Previous studies have shown poor levels of resuscitation training and knowledge among junior doctors. In addition their self reported clinical skills in managing emergency situation are low, highly variable and do not increase during their first years after graduation. However it remains to be proven whether these results of research mainly from other countries are applicable to our local population. There is currently lack of CPR research especially among junior doctors in Malaysia. The aims of this study were to determine the level of knowledge, attitude and confidence of junior doctors in HUSM and HRPZII and also to describe the factors that influence it. This study also serves as a starting point to hopefully create a database that other centers in the nation will be able to add on to. This is cross-sectional study using convenient sample. A questionnaire was design based on AHA Guidelines 2005 and review relevant literature. It was edited by two emergency physicians and pre-test was conducted in HUSM to validate and test the reliability of the questionnaire. All junior doctors in HUSM and HRPZII were included in this study. The study was conducted from October till December 2008. Questionnaires were circulated with help from representative from each hospital. It was anonymous and no time limit. The forms were then collected and coded according to the hospital and checked to confirm the doctors had trained three years and below. Statistical analysis was used using software SPSS version 12.0.1 A total of 70 junior doctors were analyzed. Average age was 26.9 years and 68.6% already in practice less than one year. 68.6% of doctors received basic resuscitation training during internship, out of these 33% had received training in previous one year. Only 11.4% had advanced training in resuscitation. 50% of doctors had attended cardiac arrest cases. However, 60% doctors never performed defibrillation. The mean knowledge score was 68%. The difference between subject variables and knowledge score was statistically not significant. The attitude score was 64.4%. 71.4% of doctors disagree their internship training was adequate and 94.3% agree all junior doctors should have ACLS. The confidence score was 28%. Most of the doctors were not confident being a team leader (85.7%), performing intubation (65.7%), defibrillation (78.6%), administering amiodarone (82.9%) and inserting central venous line (74.3%) during resuscitation. Factors that improved doctor’s confidence in resuscitation were ACLS training, more than a year job experience and completion of rotation in six departments. The resuscitation knowledge was average and most doctors have positive attitude on resuscitation. However self reported confidence doctors. Our result suggest mandatory attainment of BLS during undergraduate and ACLS during internship, increased exposure of real resuscitation situations to improve undergraduate training and regular practical/skill course six monthly.